If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-17+209=7(-9+6r)+3
We move all terms to the left:
-17+209-(7(-9+6r)+3)=0
We add all the numbers together, and all the variables
-(7(6r-9)+3)-17+209=0
We add all the numbers together, and all the variables
-(7(6r-9)+3)+192=0
We calculate terms in parentheses: -(7(6r-9)+3), so:We get rid of parentheses
7(6r-9)+3
We multiply parentheses
42r-63+3
We add all the numbers together, and all the variables
42r-60
Back to the equation:
-(42r-60)
-42r+60+192=0
We add all the numbers together, and all the variables
-42r+252=0
We move all terms containing r to the left, all other terms to the right
-42r=-252
r=-252/-42
r=+6
| d6=-10 | | -85=-4(2x+5)-1 | | –2t−(–19t)=17 | | 3(y-7)=-5y+27 | | -5n-9=34 | | 5/8b=-10 | | -6x-11=-13 | | 6^3x-5=43 | | -13x-7-x=3x+10 | | 4+9x=21 | | -4m-6=8-9m | | P/w=2/8 | | 97=1-6(-4x-8) | | -36=y-17 | | 2.5+x=5-x | | –2t−–19t=17 | | 2/2=2x-3 | | 9y-8=9y+8 | | 5x+7+9x-16+2x+23=78 | | 21/4+r=10 | | 16=b | | 5x.30=80 | | 21,5−3x=5x+1,5 | | 3x-2=-29= | | 3(5m+5)=12m+3m+9+6 | | 8x-(8x-2)=-1 | | -142=2(-8n-7) | | 3.4=~13.6+(-3.4c)+1.7c | | (12x-30)=(6x+18) | | -8(k-8)=112 | | x+16=-40 | | (h-3)=12 |